Psychopathic Traits and Recurring Victimization: An Examination Using a Community and Clinical Sample: - Daigle, Leah E. (Criminal justice and behavior, 2018)
Few studies have identified specific characteristics of recurrent victims that distinguish them from single victims. One such characteristic that may do so is possessing psychopathic traits, given that persons with psychopathic traits are generally risk-seeking, callous, short-tempered, and lack behavioral controls. To examine this possibility, we use data from both the National Longitudinal Study of Adolescent to Adult Health (Add Health) and the MacArthur Violence Risk Assessment Study (MacRisk). We find that in both samples, psychopathic traits are able to distinguish between nonvictims and recurring victims as well as single-wave victims and recurring victims. This finding holds great promise for identifying who may be at risk of experiencing recurring victimization, ways to reduce victimization risk, as well as potential additional avenues for research in this area.